ANALISIS PENGARUH PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - eni puji estuti; Putri Sendang Sari (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2023)
Abstract. At the beginning of 2020 the covid-19 pandemic began to enter Indonesia which had an impact on almost various areas of life. One of them is in the economic field, in the economic field many companies in various sectors are affected and experiencing financial difficulties. So the purpose of this research is to analyze the effect of profitability, liquidity, and leverage on financial distress. The population in this study is a manufacturing company in the consumer goods industry sub-sector which is listed on the Indonesia Stock Exchange. The technique used is a purposive sampling technique with a sample of 28 companies. The data obtained were analyzed using multiple linear regression analysis. Based on the t test obtained profitability has no effect on financial distress with the test results of a significance value of 0.318 > 0.05 and a t value of 1.009 <2.007. Liquidity has an effect on financial distress with the test results of a significance value of 0.001 < 0.05 and a t value of 3.492 > 2.007. And Leverage has no effect on financial distress with the results of testing a significance value of 0.781 > 0.05 and a t-value of 0.279 < 2.007. In the Coefficient of Determination Test, the R-Square value is 0.059, which means that the effect of profitability, liquidity and leverage on financial distress is 19.1%.